Variable sexually dimorphic gene expression in laboratory strains of Drosophila melanogaster - Dow Julian AT; Wang Jing; Meadows Lisa A; Baker Dean A; Russell Steven (BMC Genomics, 2007)
Abstract Background Wild-type laboratory strains of model organisms are typically kept in isolation for many years, with the action of genetic drift and selection on mutational variation causing lineages to diverge with time. Natural populations from which such strains are established, show that gender-specific interactions in particular drive many aspects of sequence level and transcriptional level variation. Here, our goal was to identify genes that display transcriptional variation between laboratory strains of Drosophila melanogaster, and to explore evidence of gender-biased interactions underlying that variability. Results Transcriptional variation among the laboratory genotypes studied occurs more frequently in males than in females. Qualitative differences are also apparent to suggest that genes within particular functional classes disproportionately display variation in gene expression. Our analysis indicates that genes with reproductive functions are most often divergent between genotypes in both sexes, however a large proportion of female variation can also be attributed to genes without expression in the ovaries. Conclusion The present study clearly shows that transcriptional variation between common laboratory strains of Drosophila can differ dramatically due to sexual dimorphism. Much of this variation reflects sex-specific challenges associated with divergent physiological trade-offs, morphology and regulatory pathways operating within males and females.